Business intelligence with Databricks SQL analytics : concepts, tools, and techniques for scaling business intelligence on the Data Lakehouse /: concepts, tools, and techniques for scaling business intelligence on the Data Lakehouse. (2022) - Gupta, Vihag
No abstract available